2006
DOI: 10.1016/j.cell.2006.10.029
|View full text |Cite
|
Sign up to set email alerts
|

Multipotent Embryonic Isl1+ Progenitor Cells Lead to Cardiac, Smooth Muscle, and Endothelial Cell Diversification

Abstract: Cardiogenesis requires the generation of endothelial, cardiac, and smooth muscle cells, thought to arise from distinct embryonic precursors. We use genetic fate-mapping studies to document that isl1(+) precursors from the second heart field can generate each of these diverse cardiovascular cell types in vivo. Utilizing embryonic stem (ES) cells, we clonally amplified a cellular hierarchy of isl1(+) cardiovascular progenitors, which resemble the developmental precursors in the embryonic heart. The transcription… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
889
1
23

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 967 publications
(957 citation statements)
references
References 49 publications
31
889
1
23
Order By: Relevance
“…Eomes overexpression also promoted the appearance of endothelial cells (expressing VE-cadherin and CD31; Fig 1D,E,J) and smooth muscle cells (expressing smooth muscle actin; Fig 1F,G,K and supplementary Fig S2B online). Altogether, the three types of cells derived from multipotent cardiovascular progenitors (MCPs) [27,[35][36][37] were massively increased following Eomes expression in DDM, although we cannot rule out that some endothelial and smooth muscle cells could also derive from other progenitors (such as the hemangioblasts [38] that could also be induced following Eomes expression). We and others have recently demonstrated that a combination of monoclonal antibodies (Flk1/Pdgfra) can be used to isolate the earliest Mesp1 expressing MCPs arising during ESC differentiation [16,27].…”
Section: Results and Discussion Eomes Promotes Cardiogenesis In Escmentioning
confidence: 99%
“…Eomes overexpression also promoted the appearance of endothelial cells (expressing VE-cadherin and CD31; Fig 1D,E,J) and smooth muscle cells (expressing smooth muscle actin; Fig 1F,G,K and supplementary Fig S2B online). Altogether, the three types of cells derived from multipotent cardiovascular progenitors (MCPs) [27,[35][36][37] were massively increased following Eomes expression in DDM, although we cannot rule out that some endothelial and smooth muscle cells could also derive from other progenitors (such as the hemangioblasts [38] that could also be induced following Eomes expression). We and others have recently demonstrated that a combination of monoclonal antibodies (Flk1/Pdgfra) can be used to isolate the earliest Mesp1 expressing MCPs arising during ESC differentiation [16,27].…”
Section: Results and Discussion Eomes Promotes Cardiogenesis In Escmentioning
confidence: 99%
“…Thus, by applying the appropriate concentration of SmartFlare TM Probes, which may vary in different cell types, the vast majority of a given target population should be labeled. For example, a cardiac precursor population positive for Islet1 has recently been described [35][36][37]. This rare population could be enriched by FACS sorting from iPS cultures using an Islet1-specific SmartFlare TM Probe.…”
Section: Live Screening Of Successfully Reprogrammed Murine Ttfs To Imentioning
confidence: 99%
“…22 Laugwitz et al 23 demonstrated the presence of an Isl-1 + population of cardiac stem cells in the postnatal mouse, rat, and human heart, most prominently in the outflow tract and right atrium. Further studies showed that Isl-1 marks a population of multipotent cardiac stem cells contributing to smooth muscle, endothelial, and pacemaker cell lineages in the embryonic and postnatal heart 24,25 and implicate Isl-1 + Nkx2.5 + Flk-1 + cells as the most primitive cardiac stem cells. No compelling evidence for an Isl-1 + population in the adult heart has been presented.…”
Section: Isl-1 + Cardiac Stem Cellsmentioning
confidence: 99%